Agrivoltaics across the water-energy-food-nexus in Africa: Opportunities and challenges for rural communities in Mali - Ambe Emmanuel Cheo; Nora Adelhardt; Tim Krieger; Jessica Berneiser; Federico Alberto Sanchez Santillano; Brendon Bingwa; Nischa Suleiman; Patricia Thiele; Alvaro Royes; Daniel Gudopp; Amadou Sidibé; Karim Fahmy; et al. (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2022)
Small-scale, rain-fed subsistence agriculture and pastoralism represent the major activity for Africa. For Mali, this represents about 80% of the population employed by the agricultural sector and contributes to about 42% of the Gross domestic product (GDP). The overreliance on rainfall, competing for the most valuable lands, the increasing scarcity of water, the lack of innovative technologies and infrastructure has made the agriculture sector vulnerable to climatic and non-climatic risks including an increase in the number of land conflicts. In addition, inadequate access to affordable energy has also limited social opportunities for the poor communities, especially in rural areas of Mali. Water Energy and Food (WEF) Nexus solutions such as agrivoltaics are increasingly being deployed to improve access to water for agricultural uses, improve yields and incomes, reduce drudgery especially for women, enhancing resilience and microclimate, improve land use efficiency and food security. This innovative approach has opened new prospects to improve the quality of life for people as well as their environment as a whole. Agrivoltaics is rapidly gaining popularity in many countries but not yet in African countries. This paper presents a feasibility analysis, recommendations and future directions of agrivoltaics in Mali and in Africa as a whole. Furthermore, applications of agrivoltaic systems are discussed in terms of their socio-economic and environmental effects, emphasizing also the necessity of integrative thinking in the process of strategic planning for achieving security in water, energy and food.
Keywords: 330; Nexus solutions; Climate change; Sahel region; Sub-Saharan Africa; Innovation